The Application Of Different Fresh Fish Handling Techniques On The Quality Of Raw Ingredients Of Producing Pindang Tongkol (Auxis thazard) - I Gde Suranaya Pandit; I Wayan Parwata; I Wayan Sudiarta (Warmadewa University Press, 2017)
Histamine poisoning can occur from consuming mackerel tuna fish that have undergone a process of decay. To avoid the process, the application of fresh mackerel tuna fish handling techniques required utilizing single factor completely randomized design. The treatment of fresh mackarel tuna fish handling techniques using room temperature as a treatment A.The applications of fresh mackarel tuna fish handling techniques with the addition of crushed ice (1: 4) as treatment B. The application of fresh mackarel tuna fish handling techniques with the addition of 10% salt as treatment C, as well as fish the applications of mackarel tuna fresh handling technicques with 50% B and 50% C as a treatment D. Transportation starts from the fish handling sites in Seraya village Karangasem towards the fish auction in the village of Kusamba Klungkung Bali for Â±3 hours. Results of analysis of variance showed significant differences (P